2003
DOI: 10.1111/j.1744-6171.2003.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Communication Skills Training on Parents and Young Adolescents From Extreme Family Types

Abstract: This universal, community-based, family-focused intervention may not be indicated for extreme families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
0
9
0
4
Order By: Relevance
“…Resilience is an outcome of the original or higher levels of balance; therefore it might provide a successful compatibility in life (30). According to experts, different skills of resilience are possible to learn (31,32), therefore, the level of mental and emotional health of people can be enhanced by teaching these skills. Individuals who take advantage of problem-oriented coping styles to experience bravery or risk taking more effectively enjoy their socially intimate relationships which in turn leads toward less passiveness, anxiousness, and depression (33).…”
Section: Discussionmentioning
confidence: 99%
“…Resilience is an outcome of the original or higher levels of balance; therefore it might provide a successful compatibility in life (30). According to experts, different skills of resilience are possible to learn (31,32), therefore, the level of mental and emotional health of people can be enhanced by teaching these skills. Individuals who take advantage of problem-oriented coping styles to experience bravery or risk taking more effectively enjoy their socially intimate relationships which in turn leads toward less passiveness, anxiousness, and depression (33).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important for clinicians to note that research has demonstrated that family communication patterns can be altered and improved through training in communication skills (Riesch et al, 2003). This is especially true as children approach adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true as children approach adolescence. Riesch et al (2003) note, "Participation in communication training by families who are on the cusp of adolescence may improve family relationships and communication, which, in turn, may promote optimal developmental outcomes among adolescents" (p. 164). As Forrest et al (2003) have indicated, this information may be particularly helpful to HD families struggling with disclosure issues as the children approach adolescence and the time is coming for "key life decisions" (p. 324).…”
Section: Discussionmentioning
confidence: 99%
“…Bu süreçte çıkabilecek sorunları önlemek insanlar arası ilişkilerde iletişim kopukluklarını engelleyebilecek, buna bağlı olarak da ilişkileri daha sağlıklı kılabilecektir. Bunun yanı sıra bireyler arasında doğabilecek sorunların çözümlenmesi de bu sorunun iyi ifade edilebilmesiyle bağlantılıdır (3). Bu da bir takım iletişim becerilerini bilmekle sağlanabilir.…”
Section: Introductionunclassified
“…Bu sebeple iletişim becerilerini geliştirmek amacıyla hazırlanan, iletişim becerileri eğitim programlarının etkililiğini ölçmek amacıyla birçok çalışma yapılmıştır. Bu çalışmalarda genel olarak iletişim becerileri eğitim programlarının, iletişim becerilerini geliştirdiği görülmüştür (4,6,7,3,8,9). Ayrıca yalnızlık ve çatışma eğilimi gibi faktörler üzerinde pozitif etkileri olduğu da belirtilmiştir (10,11,12,13,14).…”
Section: Introductionunclassified